Morbiditätsprofil von Hochleistungsfechtern - Wild, A.; Jäger, M.; Pöhl, C.; Werner, A.; Raab, P.; Krauspe, R. (Sportverletzung Sportschaden, 2001)
There are only very few data available about the morbidity of elite fencers athletes. The aim of this study was to elucidate the nature and history of the morbidity in high-performance fencers. The injury profile over 15 years of 93 fencers at a highly competitive level was analysed by clinical assessment and examination. We found a positive correlation between the injured upper extremity with the dominant fencing side while the lower extremity showed no side preference with regard to vulnerability. Achillodynia occurred more frequently at the contralateral side. The joint most affected was the knee. The dominating symptom was patellofemoral pain which occurred in 39.8 %.